The Impact of Foreign Direct Investment on China’s Carbon Emissions - Fangmiao Hou (MDPI AG, 2021)
China is world renowned for its significant achievements in several fields. China’s economic growth has been prominent, with the country’s GDP ranking second globally. China’s Foreign Direct Investment (FDI) inflows have been significant, with the country now known as the second largest economy in the world. FDI however does have some negative consequences on China’s environment. While attracting FDI promotes economic growth through industrial upgrading, the deleterious impacts of the latter on the environment cannot be ignored. The current study analyses the actual use of FDI and carbon emissions in China from 1997 to 2018. Quantitative analysis was employed to analyze the trends of FDI and carbon emissions in China as a whole and in the respective regions, namely the eastern, central and western regions. Regression analysis was then conducted to analyze the impact of FDI on carbon emissions in China on the national level and regional levels, i.e., in the eastern, central and western regions. The conclusion of this article is that FDI will play a positive role in China’s overall carbon emissions. The study has important implications for policy. We recommend that the corresponding investment policies need to be formulated according to the different levels of economic development among the regions.